Gabriel Harvey and the History of Reading Essays by Lisa Jardine and others - Grafton, Anthony; Popper, Nicholas; Sherman, William (UCL Press, 2024)
Few articles in the humanities have had the impact of Lisa Jardine and Anthony Grafton's seminal 'Studied for Action' (1990), a study of the reading practices of Elizabethan polymath and prolific annotator Gabriel Harvey. Their excavation of the setting, methods and ambitions of Harvey's encounters with his books ignited the History of Reading, an interdisciplinary field which quickly became one of the most exciting corners of the scholarly cosmos. A generation inspired by the model of Harvey fanned out across the world's libraries and archives, seeking to reveal the many creative, unexpected and curious ways that individuals throughout history responded to texts, and how these interpretations in turn illuminate past worlds. Three decades on, Harvey's example and Jardine's work remain central to cutting-edge scholarship in the History of Reading. By uniting 'Studied for Action' with published and unpublished studies on Harvey by Jardine, Grafton and the scholars they have influenced, this collection provides a unique lens on the place of marginalia in textual, intellectual and cultural history. The chapters capture subsequent work on Harvey and map the fields opened by Jardine and Grafton's original article, collectively offering a posthumous tribute to Lisa Jardine and an authoritative overview of the History of Reading.